6x+9=-2(x+1)

Simple and best practice solution for 6x+9=-2(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+9=-2(x+1) equation:


Simplifying
6x + 9 = -2(x + 1)

Reorder the terms:
9 + 6x = -2(x + 1)

Reorder the terms:
9 + 6x = -2(1 + x)
9 + 6x = (1 * -2 + x * -2)
9 + 6x = (-2 + -2x)

Solving
9 + 6x = -2 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
9 + 6x + 2x = -2 + -2x + 2x

Combine like terms: 6x + 2x = 8x
9 + 8x = -2 + -2x + 2x

Combine like terms: -2x + 2x = 0
9 + 8x = -2 + 0
9 + 8x = -2

Add '-9' to each side of the equation.
9 + -9 + 8x = -2 + -9

Combine like terms: 9 + -9 = 0
0 + 8x = -2 + -9
8x = -2 + -9

Combine like terms: -2 + -9 = -11
8x = -11

Divide each side by '8'.
x = -1.375

Simplifying
x = -1.375

See similar equations:

| 4x^2y^3-12x^2y^2+8xy^2= | | 6t-12=-52+t | | g(x)=3x^2+4 | | .04(3x-1)+.9(x-3)=-.18 | | 0=16-(x*1.19-x*1.19*0.02) | | 49x^2y+7xy^3=0 | | 2y+6x=-4 | | 10x-11=3x+8 | | 27q^2-15=33 | | x^2-9/4=0 | | 12(0+x)=36 | | 0=16-(x-x*0.02*1.19) | | 3+7x=-3+x | | 4(5-4x)=148 | | 25-2y=3y-35 | | 2/3n^2-11=-3 | | 6(10+5x)=360 | | 3n^2-17=3 | | 2x-2=6x+26 | | 15+6z=-15 | | -7c^2=-100 | | 2x+32=12x-45 | | 4(x-1)=12x | | -7n+4a=x | | 4+2(8w+6)= | | 1=12*x^2+11*x | | 16=x-(x*0.02*1.19) | | 2(1-5x)=72 | | 12(3-3x)=60 | | 4b^2-5=-7 | | 2x+6=-18-4 | | 4(2-x)=5(x+1) |

Equations solver categories